Transport of oxytocin to the brain after peripheral administration by membrane‐bound or soluble forms of receptors for advanced glycation end‐products. (18th March 2021) - Munesue, Sei‐ichi; Liang, MingKun; Harashima, Ai; Zhong, Jing; Furuhara, Kazumi; Boitsova, Elizabeta B; Cherepanov, Stanislav M; Gerasimenko, Maria; Yuhi, Teruko; Yamamoto, Yasuhiko; Higashida, Haruhiro
Abstract: Oxytocin (OT) is a neuropeptide hormone. Single and repetitive administration of OT increases social interaction and maternal behaviour in humans and mammals. Recently, it was found that the receptor for advanced glycation end‐products (RAGE) is an OT‐binding protein and plays a critical role in the uptake of OT to the brain after peripheral OT administration. Here, we address some unanswered questions on RAGE‐dependent OT transport. First, we found that, after intranasal OT administration, the OT concentration increased in the extracellular space of the medial prefrontal cortex (mPFC) of wild‐type male mice, as measured by push‐pull microperfusion. No increase of OT in the mPFC was observed in RAGE knockout male mice. Second, in a reconstituted in vitro blood‐brain barrier system, inclusion of the soluble form of RAGE (endogenous secretory RAGE [esRAGE]), an alternative splicing variant, in the luminal (blood) side had no effect on the transport of OT to the abluminal (brain) chamber. Third, OT concentrations in the cerebrospinal fluid after i.p. OT injection were slightly higher in male mice overexpressing esRAGE (esRAGE transgenic) compared to those in wild‐type male mice, although this did not reach statistical significance. Although more extensive confirmation is necessary because of the small number of experiments in the present study, the reported data support the hypothesis that RAGE may be involved in the transport of OT to the mPFC from the circulation. These results suggest that the soluble form of RAGE in the plasma does not function as a decoy in vitro. Abstract : RAGE is involved in the transport of oxytocin to the brain from the circulation. The soluble forms of RAGE in the plasma do not inhibit nor facilitate membrane RAGE‐dependent oxytocin transport, but may function as a buffer of plasma oxytocin.